A face for picasso eaudiobook Coming of age with crouzon syndrome. - Henley, Ariel (Recorded Books, Inc., 2021)
There was danger in the kind of beauty I was desperate to achieve. At only eight months old, identical twin sisters Ariel and Zan Henley were diagnosed with Crouzon syndrome—a rare condition where the bones in the head fuse prematurely. They were the first twins known to survive it. Growing up, Ariel and her sister endured numerous medical procedures to keep them alive. Doctors expanded the twins' skulls and broke bones to make room for their growing organs. After each surgery, the sisters felt like strangers to each other, unable to recognize themselves in the mirror. Their case attracted international attention. A French fashion magazine said Ariel and Zan "resembled the works of Picasso," as if they were abstract paintings, not girls just trying to survive. Later, plastic surgeons cut and trimmed and tugged their faces toward a tenuous aesthetic ideal. The girls dreamed of appearing "beautiful" but would settle for "normal." Fighting for acceptance was a daily chore. Between besting middle school bullies, becoming a cheerleader in high school, and finding her literary voice in college, Ariel learned to navigate a beauty-obsessed world with a facial disfigurement to become the woman she is today. From a resonant new voice, here is an unforgettable young adult memoir about beauty, sisterhood, and the strength it takes to put your life—and yourself—back together, time and time again.